2010
DOI: 10.1519/jsc.0b013e3181e27245
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anthropometric and Physical Performance Profiles of Young Elite Male Soccer Players: A Longitudinal study

Abstract: The purpose of the present longitudinal study was to explore distinctive anthropometric and physical performance characteristics of young soccer players between the age of 11 and 14 and to reveal the performance at the age of 11, which contributes to the later success. Male players of the best national male squads of the 'cadet league' (14 years of age; n = 26) were annually tested starting from the age of 11 for body size and composition, flexibility, power, coordination, and agility. Randomly selected untrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 11 publications
5
36
0
1
Order By: Relevance
“…Studies among youth and adolescent males of different nationalities suggest that body size contributes relatively little to variation in performance in these players and that the variation is probably mostly due to biological maturity (Beunen, Ostyn, Simons, Renson, & Van Gerven, 1981;Malina et al, 2005;Malina, Eisenmann, Cumming, Ribeiro, & Aroso, 2004;Reilly et al, 2000), as youth selections tend to favor players who are advanced in biological maturation (Coelho E Silva et al, 2010;Sarmento, Anguera, Pereira, & Araujo, 2018). Studies comparing youth and adolescent elite male soccer players to control groups did not find any differences in body size between the groups (Franks, Williams, Reilly, & Nevill, 1999;Mirkov, Kukolj, Ugarkovic, Koprivica, Vladimir & Jaric, 2010), suggesting young players' movement agility and coordination are the best predictors of future performance in soccer (Mirkov et al, 2010; however, see Gravina et al, 2008). Reilly, Bangsbo, and Franks (2000) reviewed the literature on anthropometric and physiological characteristics of adolescent and adult soccer players and concluded that it is not possible to isolate individual prerequisites for success (including height) with great confidence.…”
Section: Body Size Of Professional Football Playersmentioning
confidence: 99%
“…Studies among youth and adolescent males of different nationalities suggest that body size contributes relatively little to variation in performance in these players and that the variation is probably mostly due to biological maturity (Beunen, Ostyn, Simons, Renson, & Van Gerven, 1981;Malina et al, 2005;Malina, Eisenmann, Cumming, Ribeiro, & Aroso, 2004;Reilly et al, 2000), as youth selections tend to favor players who are advanced in biological maturation (Coelho E Silva et al, 2010;Sarmento, Anguera, Pereira, & Araujo, 2018). Studies comparing youth and adolescent elite male soccer players to control groups did not find any differences in body size between the groups (Franks, Williams, Reilly, & Nevill, 1999;Mirkov, Kukolj, Ugarkovic, Koprivica, Vladimir & Jaric, 2010), suggesting young players' movement agility and coordination are the best predictors of future performance in soccer (Mirkov et al, 2010; however, see Gravina et al, 2008). Reilly, Bangsbo, and Franks (2000) reviewed the literature on anthropometric and physiological characteristics of adolescent and adult soccer players and concluded that it is not possible to isolate individual prerequisites for success (including height) with great confidence.…”
Section: Body Size Of Professional Football Playersmentioning
confidence: 99%
“…The authors found that both stature and maturity status were significant contributors to vertical jump performance when young soccer players progress into puberty. As previously stated, several factors have an impact on muscle force development, however only a few studies have highlighted the influence of motor coordination [16,24,27]. A review by Van Praagh and Doré [43] suggested that improved movement coordination is a more important contributor to muscle force gain in complex, multi-joint exercises, such as vertical jump and sprinting.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Children can be given these exercises at the age of 5 to display the strategies used to acquire the suitable motor skills and these characteristics should be continued in particular during the critical development stage between the ages of 9-12 [5]. Mirkov et al (2010) have stated that agility and coordination are important factors in the future success of athletes aged 11 [17]. During this period, which provides a structure to learn movement models, timing, balance and coordination, planned exercises should be higher in number [2].…”
Section: Introductionmentioning
confidence: 99%